Quality management practices system in palm oil supply chain: the case of upstream / Hidayatul Husna Samsudin - Samsudin, Hidayatul Husna (Faculty of Plantation and Agrotechnology, 2019)
Some oil palm organizations have yet developed a tool to access quality management practices in the upstream. Upstream in oil palm supply chain include the growing sector involved in the cultivation of oil palm that include nursery establishment and production of Fresh Fruit Bunches (FFB). Besides, oil palm industry players have raised and issued that the quality management practices are not continuously been practiced despite existing various current quality management practices implemented in palm oil industry today. This research attempts to identify the current quality management practices in palm oil upstream supply chain and ultimately develop a tool for assessing quality management practices for industry by using qualitative method. This research uses Design Science Research Methodology as a framework and used grounded theory methods for the Quality Management Practices Model (QMPPOSC). The tool consists of 2 modules and each contains 2 parts which are operation and sustainability. 2 companies (FELDA and Private Plantation Company) have been sampled to evaluate the parameters and contents of the tool. The companies that have been evaluated scored 4 and 5 stars out of 5. This research has not concluded that the Quality Management Practices Model (QMPPOSC) is the solution to the existed problem, but merely a solution. This tool is created to help the industries to evaluate their sustenance of plantation operation in quality management practices. QMPPOSC is roadmap towards quality management practices that eventually will help in generate profit in the future.